Leitura como letramento: perspectivas críticas para a prática docente em aulas de língua inglesa - Stefani Moreira Aquino Toledo (2021)
The present paper consists of a case study, which investigated the possible impacts of critical literacy on the teaching practice of an English language teacher in the context of the COVID-19 pandemic in a state public school located in a city in the north of Minas Gerais. It aimed to understand the possible effects and limitations of the assumptions of the critical literacy theory in the pedagogical practice of the teacher through the design and application of a reading activity in the light of this theory for students of the 3rd year of high school. Theoretical contributions related to critical literacy were used, having as references the Brazilian Curriculum Guidelines for High School (OCEM) (BRASIL, 2006), Menezes de Souza (2011) and Duboc (2015). In addition, this qualitative research relied on some data generation instruments applied to the teacher such as semi-structured online questionnaire, oral semi-structured interviews and reflective diaries. Moreover, a semi-structured questionnaire was also applied to her students about their impressions on the non-presential activities and the reading activity proposed. The results of the analysis pointed out some challenges imposed by the new context on a pedagogical practice focused on a critical attitude, for example, the lack of communication among the teacher and her students in order to promote the education of the student-reader-citizen (BRASIL, 2006). Furthermore, the analysis showed that, more than understanding the process of preparing and applying the reading activity, it was also possible to develop a training process between participating teacher and researcher, so that one could contribute to the practice of the other. Finally, this research brings implications for the practice of public basic education English teachers as well as for the possibilities of adopting a pedagogical practice focused on the studies of critical literacy, even in times of a pandemic.